Branching ratios for the reactions of OH with ethanol amines used in carbon capture and the potential impact on carcinogen formation in the emission plume from a carbon capture plant. Issue 38 (10th September 2015) - Onel, L.; Blitz, M. A.; Breen, J.; Rickard, A. R.; Seakins, P. W.
Abstract : Branching ratios for the OH reaction with ethanol amines and potential risk of carcinogenic formation in the carbon capture plume. Abstract : The OH initiated gas-phase chemistry of several amines that are potential candidates for use in post-combustion carbon capture (PCCC) plants have been studied by laser flash photolysis with OH monitored by laser induced fluorescence. The rate coefficients for the reaction of OH with N -methylethanolamine (MMEA) and N, N -dimethylethanolamine (DMEA) have been measured as a function of temperature (∼300–500 K):, . The results for DMEA lie between previous values. This is the first kinetic study of the OH + MMEA reaction. At low pressures in the presence of oxygen, OH is recycled in the DMEA reaction as has been observed for other tertiary amines. Branching ratios for OH abstraction with MEA, DMEA and MMEA are dominated by abstraction from the α CH2 group. Abstraction from N–H is determined to be 0.38 ± 0.06 for MEA and 0.52 ± 0.06 for MMEA at 298 K. The impact of these studies has been assessed by using a modified chemical box model to calculate downwind concentrations of nitramines and nitrosamine formed in the photo-oxidation of MEA. Under clear sky conditions, the simulations suggest that current safe guidelines for nitramines may be significantly exceeded with predicted MEA emission rates.